2004
DOI: 10.1074/jbc.m403985200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of ThiH, a Member of the Radical S-Adenosylmethionine (AdoMet) Protein Superfamily

Abstract: Thiamine pyrophosphate (TPP) is an essential cofactor for all forms of life. In Salmonella enterica, the thiH gene product is required for the synthesis of the 4-methyl-5-␤ hydroxyethyl-thiazole monophosphate moiety of TPP. ThiH is a member of the radical S-adenosylmethionine (AdoMet) superfamily of proteins that is characterized by the presence of oxygen labile [Fe-S] clusters. Lack of an in vitro activity assay for ThiH has hampered the analysis of this interesting enzyme. We circumvented this problem by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…Complementation of two of the growth defects required restoration of the low flux thiamine biosynthesis pathway (the amount of thiamine pyrophosphate in wild-type S. enterica grown in minimal glucose medium is 41.4 pmol/mg dry weight (46)). Stains lacking apbC and yggX (or purF) are thiamine auxotrophs likely because of poor cluster occupancy of ThiH/ThiC (47,48,80). Complementation of a third growth defect required function of the high flux tricarballylate catabolic metabolic pathway (35,37,49,50).…”
Section: Protein Sequence Alignments Show Significant Conservation Ofmentioning
confidence: 99%
“…Complementation of two of the growth defects required restoration of the low flux thiamine biosynthesis pathway (the amount of thiamine pyrophosphate in wild-type S. enterica grown in minimal glucose medium is 41.4 pmol/mg dry weight (46)). Stains lacking apbC and yggX (or purF) are thiamine auxotrophs likely because of poor cluster occupancy of ThiH/ThiC (47,48,80). Complementation of a third growth defect required function of the high flux tricarballylate catabolic metabolic pathway (35,37,49,50).…”
Section: Protein Sequence Alignments Show Significant Conservation Ofmentioning
confidence: 99%
“…These observations suggest the possibility of chemical iron sulfur cluster reconstitution and an AdoMet-driven reaction, most likely that of ThiH. Mutagenesis of the highly conserved cysteine-rich motif from Salmonella enterica ThiH suggested that these residues function as ligands to the [4Fe-4S] cluster (16).…”
mentioning
confidence: 99%
“…Whole cell feeding studies in E. coli and knock-out mutants thereof indicated that Thz-P synthesis is dependent on the precursors tyrosine, cysteine, and 1-deoxy-xylulose-5-phosphate (Dxp) and the enzymes ThiFSGH, ThiI, and IscS (4,10,(12)(13)(14)(15)(16). The Thz-P pathway in B. subtilis is significantly different, since the oxygensensitive iron sulfur cluster-containing enzyme ThiH is replaced by ThiO, an oxygen-tolerant FAD-dependent oxidase.…”
mentioning
confidence: 99%
“…Along with mutations in the isc operon, mutations in the four loci described above cause a conditional thiamine auxotrophy in S. enterica attributed to impaired assembly or repair of the Fe-S cluster in the ThiH enzyme (14,25,42). In addition to this thiamine requirement, one of the defining features of this class of mutants was the observation that the expression of yggX suppressed the thiamine auxotrophy of each (13).…”
mentioning
confidence: 99%
“…In S. enterica, rseC is the fourth gene in the rpoE operon, although no connection between rseC and rpoE regulation has been found. In E. coli, mutations in this gene were isolated because they caused constitutive expression of the SoxRS regulon (18), leading to the hypothesis that RseC is involved in the reduction of the Fe-S clusters in SoxR after recovery from oxidative stress (18).Along with mutations in the isc operon, mutations in the four loci described above cause a conditional thiamine auxotrophy in S. enterica attributed to impaired assembly or repair of the Fe-S cluster in the ThiH enzyme (14,25,42). In addition to this thiamine requirement, one of the defining features of this class of mutants was the observation that the expression of yggX suppressed the thiamine auxotrophy of each (13).…”
mentioning
confidence: 99%